Introduction to the Special Issue on Dialogue 2.0: New Perspectives, Enduring Challenges, and Promising Directions. (December 2020) - Jameson, Jessica Katz; Lee, Nicole M.
The current state of polarization evidenced in communication around race, politics, criminal justice, immigration, health care, and other critical social issues highlights the challenges of talking about our most enduring, "wicked" problems. This increased polarization has been shown to result in self-monitoring of media consumption (both traditional and social) such that people are more likely to engage with sources that support existing beliefs rather than seek information that crosses views and values. The motivation for this special issue came from an interdisciplinary symposium hosted by North Carolina State University's Communication, Rhetoric and Digital Media (CRDM) doctoral program that took place from 28 March to 30 March 2019 and included participants from across the United States. The symposium was titled "Dialog 2.0: Social Movements, Online Communication and Transformation." The seven articles that comprise this special issue include symposium participants along with the voices of other scholars around the world who are thinking about and investigating social media and dialogic communication. While the authors in this special issue offer different conceptions of dialogue, it is broadly conceived as communication that is inclusive of multiple voices (especially those that have been marginalized) and aimed at improving understanding rather than persuading or "winning."